Parpol, Pemilu dan Demokrasi: Dinamika Partai Politik dalam Sistem Pemilihan Umum di Indonesia Perspektif Demokrasi - Udiyo Basuki (Kosmik Hukum, 2020)
In a democratic country the relationship between the state and the people must be a reflection of a mutualistic symbiosis. This means that these relationships must be mutually dependent and mutually beneficial. This relationship will be evident when the political system developed by a country provides sufficient space for political activities in the community. This space for political activity will give color to democratic life in a country. The principle of democracy and people's sovereignty requires people's participation in the life of the state administration. People or citizens are not only objects, but subjects and play an important role in the life of the state. For this reason, the existence of a representative institution is an absolute that must be fulfilled in a democratic country with people's sovereignty. According to modern democracy, political parties, general elections and representative institutions are three institutions that cannot be separated from one another. That every political party will always strive to gain large popular support during general elections so that the representative institution can be dominated by the political party concerned.Keywords: political parties, general elections, democracy.